Application of the Weighted Product (WP) Method in the Decision Support System for Determining the Best Employee Case Study of Pt Alno Air Ikan Estate - Yanto, Reno Hendra; Sari , Herlina Latipa; Sudarsono , Aji (Jurnal Komputer, 2022)
PT. Alno Air Ikan Estate is a company engaged in the oil palm and rubber plantations located in Mukomuko Regency, Bengkulu Province. PT Alno Air Ikan Estate is still using conventional methods to determine the best employees so it requires a decision support system that can correct weaknesses. One of the Decision Support System methods is Weighted Product (WP). This method is the method used in the simplest ranking of values ​​by using multiplication to relate rating attributes where the rating must first be raised to the weight of the attribute in question. Application Application of the weighted product (WP) method in a decision support system to determine the best employee, can be used to determine the best employee based on criteria, namely attendance value, years of service, attitude, and supporting elements. Based on the research results of the 15 samples used in the application of the weighted product (WP) method in the decision support system for determining the best employee, the best employee is Joko Purwanto with a value of 0.09. This application is made using the Visual Basic Net programming language with SQL server database. The author's suggestion is that this new system should be used as a basis for improving the old system at PT. Alno Air Fish Estate which is still manual.